Tata Kelola Perusahaan Dan Pengakuan Pendapatan Prematur - Maria Theresia Irlene; Ari Budi Kristanto (AFRE (Accounting and Financial Review), 2020)
The purpose of this research is to observe an influence between corporate governance and premature revenue recognition. There are 167 manufacturing companies listed on the IDX, then through a sample collection method using purposive sampling and 37 companies acquisition for three years. The analytical technique used is the regression of data panels with common effect models with GLS calculations. The results indicate that the number of the board of directors, the number of audit committee meetings, the financial skills of the audit committee negatively affect premature revenue recognition, and the number of the board of commissioners who are not as influential premature revenue recognition. Therefore, the recommendation for governments and companies is to create new governance standards to limit earnings management actions that are detrimental to the parties. This study also used as other empirical evidence regarding the relationship of corporate governance to the premature revenues recognition and renewing vulnerable testing time. DOI: https://doi.org/10.26905/afr.v3i1.4293